Extra-fascial hemithyreoidectomy - D. I. Malinin; V. G. Petrov (Бюллетень сибирской медицины)
The aim of the study was to improve surgical results of patients having thyroid gland pathology by the development of the surgery method directed to increasing possibility of injury and maintenance of the upper laryngeal nerve integrity. Method of performing extrafascial hemithyreoidectomy with visualization of recurrent nerve, parathyroid gland and upper thyroid artery is presented which is directed to decrease specific complications (vocal fold paresis, hypoparathyreosis) and complications associated with the upper laryngeal nerve injury. Using this method, 166 patients having node pathology of thyroid gland were operated on. This method resulted in decreased number of complications (from 15,0 to 2,6%).